2022
DOI: 10.14309/ctg.0000000000000491
|View full text |Cite
|
Sign up to set email alerts
|

Fecobionics Evaluation of Biofeedback Therapy in Patients With Fecal Incontinence

Abstract: INTRODUCTION: Biofeedback therapy (BFT) is a well-known treatment for functional anorectal disorders. The effect of BFT was monitored in fecal incontinence (FI) patients with the Fecobionics test and with the conventional technologies, anorectal manometry (ARM) and balloon expulsion test (BET). METHODS:Studies were performed in 12 patients before and after 8 weeks of biofeedback training. The Fecal Incontinence Severity Index (FISI) score was obtained. Anal resting and squeeze pressures were measured before t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 42 publications
(93 reference statements)
0
2
0
Order By: Relevance
“…The problem of faecal and urinary incontinence is a debilitating condition, both physically and psychologically, that has a significant negative impact on quality of life [17].…”
Section: The Problem Of Faecal and Urinary Incontinencementioning
confidence: 99%
“…The problem of faecal and urinary incontinence is a debilitating condition, both physically and psychologically, that has a significant negative impact on quality of life [17].…”
Section: The Problem Of Faecal and Urinary Incontinencementioning
confidence: 99%
“…It was demonstrated that the axial pressure signatures, preload-afterload analysis, and computation of defecation indices (DIs) with Fecobionics provide useful endpoints 17 , 25 . Studies have also been published on patients with fecal incontinence and obstructed defecation 18 , 21 , 23 , 26 , since these symptoms play a crucial role in the clinic 1 , 12 , 15 , 27 , 28 . However, only few studies have been published with technology that allows integrated measurements of the various mechanisms controlling continence and defecation.…”
Section: Introductionmentioning
confidence: 99%